Mothers' Union Statuses and Their Involvement in Young Children's Schooling. Issue 1 (20th October 2016) - Ressler, Robert W.; Smith, Chelsea; Cavanagh, Shannon; Crosnoe, Robert
Abstract: U.S. schools often expect the educational involvement of parents, which may be facilitated when parents have partners, especially a partner also invested in the child. As such, parental involvement at school and at home could be a channel of the diverging destinies of U.S. children from different families. This study applied fixed effects modeling to the Early Childhood Longitudinal Study–Kindergarten Cohort to examine the link between mothers' union statuses and their involvement behaviors. Being partnered appeared to benefit mothers' school and home involvement when children were in the primary grades, with little evidence of an additional benefit from that partnership being marital. A biological tie between the male partner and the child only seemed to matter for mothers' school involvement. These patterns did not vary by family income, maternal depression, or maternal employment, but they were stronger when children were just beginning schooling.